New Challenges to Ageing in the Rural North A Critical Interdisciplinary Perspective - Naskali, Päivi; Harbison, Joan R.; Begum, Shahnaj (International Perspectives on Aging, 2019)
This book provides an underexplored view of ageing, one that conceives older people as valuable resources in their communities, as active citizens with both voice, and an agency that includes the capacity for resistance. It acknowledges that becoming old with dignity means also paying attention to caring, good health services and the possibility of good death. The book defines age and ageing as multiple, culturally and historically constructed phenomena that are only loosely connected to the years of one's life. In focusing on the peripheral North located in the Nordic, Canadian and Russian north, it highlights important questions and viewpoints that can be found and adapted to other rural areas. The book answers the following questions: What is the relevance of legislation and international legal agreements in ensuring the rights of elderly people under political and economic changes? What challenges do geographic isolation, changing age structure, and cultural and ecological transformations pose to possibilities for meeting older people's needs for engagement in society as well as for their care? As such this book will be of interest to all those working in population aging.